Working More and Feeling Better: Women's Health, Employment, and Family Life, 1974-2004 - Schnittker, Jason (American Sociological Review, 2007)
Women have long reported worse self-rated health than men. This difference, however, may be changing. Rising educational attainment and labor force participation over the last two decades may have improved women's health, yet some have speculated that such benefits are increasingly threatened by a variety of other important changes, including growing difficulty balancing work and family. This article explores trends in women's health, employment, and family life between 1974 and 2004, using the cumulative General Social Survey and recent waves of the National Health Interview Survey, focusing specifically on the relationship between work hours, family responsibilities, and self-rated health. On the one hand, the results are consistent with research and speculation regarding health and women's changing roles. More women are employed and working longer hours, often combining work with parenting. Furthermore, the health benefits of employment decline somewhat when employment is combined with the care of a young child. Nevertheless, women reported much better health in the 1990s than they did in earlier periods and the gender gap has narrowed. The upward trend in women's absolute health reflects a progressive increase in women's education, while the closing of the gender gap reflects women's growing rates of labor force participation. These positive health trends will likely continue in the future. Indeed, judging from evidence among some select groups-including the college educated and those working fulltime- the well-known gender gap in self-rated health might soon reverse, mitigating patterns once thought rooted in more innate sex differences.